Above the hoof: functional morphology of the fossil deer from Tegelen, the Netherlands. (10th September 2014) - Alcalde, Gema M.; van den Hoek Ostende, Lars W.; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> Villafranchian faunas were widely spread throughout the European continent during the Plio‐Pleistocene. Ungulates, and particularly ruminants, are very well represented in most of the localities of this period. The fossil site of Tegelen (Province of Limburg, the Netherlands) is a classical Villafranchian locality where cervids are especially abundant. Some of the sites from this period have been thoroughly studied in various aspects, such as faunal assemblages, biochronology, magnetostratigraphy, sedimentology or palaeoenvironmental conditions, among others. Tegelen has been as well studied, but its particular exploitation has hampered its study for years. In order to reconstruct its prevailing palaeohabitat, we have applied statistical analyses based on functional morphology for the first time for this fossil site. In this work, we have analysed the ecomorphology of the postcranial skeleton of Eucladoceros ctenoides and Metacervoceros rhenanus, the two extinct species of deer present in Tegelen. Results show that the best ecological indicators are the metapods and the tibia, while the astragalus seems to be the least informative element. The analyses reveal likewise how both taxa show adaptations to both open and forest environments, but with a slight trend to the former. These results disagree with the general assumption that E. ctenoides and M. rhenanus are indicative of forested settings, as well as with the classical interpretations of the palaeoenvironment of Tegelen made to date, which are exclusively based on the fauna. However, they go along with the appearance of some taxa typical of open habitats, such as the micromammals Hystrix and Dicrostonyx, which could help to explain their enigmatic presence. Copyright © 2014 John Wiley & Sons, Ltd.